Mężczyźni w zawodach kobiecych – projekty zorientowane na wsparcie zatrudnienia mężczyzn w placówkach przedszkolnych Niemiec - Nowosad, Inetta (Adult Education Discourses, 2020)
The article focuses on the ways of implementing gender equality policies in Germany, as exemplified by pre-school staff. Today, model projects supported by the federal government are designed to overcome social stereotypes and bring measurable results. There is a clear departure from the original vision of the profession, which at its source was directed only at women, and as a result, it is also feminised nowadays. This situation, constant for nearly 200 years, is the result of disregarding the rank of this professional group in the political discourse and treating it as “invisible”. The current governmental policies support the employment of men at preschools, so the present-day status is slowly changing. The purpose of the article is to present the main model projects implemented in the last decade by all federal states supported by the federal government, but also to analyse their key assumptions and the adopted arguments. The government’s involvement in the implementation of projects focused on supporting the employment of men in pre-school institutions and monitoring their results, can be seen as examples of practical gender equality policies. As a result, a very interesting picture emerges, in which general issues that are present in social debates (gender) have been combined with the specifics for the professional group “ErzieherIn”, such as, increasing the rank of early care and education, but also serious staff shortages. Tensions in this field influence the pace of change in which tradition is giving way to contemporary social expectations.